Performance of an aerobic granular sequencing batch reactor fed with wastewaters contaminated with Zn2+ - Marques, Ana P. G. C. (2014)
The main aim of this study was to investigate the performance of an aerobic granular sludge sequencing batch reactor (AGS-SBR) receiving water streams supplied with different loads of Zn2+ (50 and 100 mg L-1) during an operation of 866 cycles (ca. 109 days). When the metal was not fed, chemical oxygen demand (COD), PO43- and NH4+ were efficiently removed, with efficiencies of 56, 23 and 72% respectively. DGGE profiles showed that Zn2+ supply negatively affected the bacterial diversity and community structure of the granules. Consequently, the shock loadings with Zn2+, particularly at the higher levels (100 mg L-1), affected the nutrient removal in the AGS-SBR, although the reactor still generally complied with admissible legal values concerning organic matter, nitrogen and Zn. Simultaneous removal of PO43- and TSS in such conditions needs further refining but the application of aerobic granular SBR in the treatment of Zn2+ contaminated wastewaters seems viable.